Interpelação ética da alteridade na constituição da subjetividade: um diálogo entre Emanuel Levinas e Davi Kopenawa - Sestari, Edson (Universidade do Vale do Rio dos Sinos, 2024)
The thesis, titled The Ethical Interpellation of Alterity in the Constitution of Subjectivity: A Dialogue between Emmanuel Levinas and Davi Kopenawa, explores the complex intersection between the ethics of alterity as proposed by Emmanuel Levinas and the Yanomami worldview, articulated by Davi Kopenawa. The research begins by critically engaging with Heideggerian ontology and the individualistic paradigm that characterizes Western culture, seeking in Levinas an alternative that centers the relationship with the Other in the constitution of subjectivity. The study proposes that Levinasian ethics, with its focus on unconditional responsibility for the Other, offers a powerful response to the crisis of fragmentation and isolation generated by Western hyperindividualism. Levinas challenges the primacy of ontology, proposing an ethics in which the Other is not merely one being among others, but rather an infinite call that demands an ethical response transcending the logic of totality. In contrast, the Yanomami worldview presented by Kopenawa deeply critiques Western culture, pointing to the devastating consequences of its relentless pursuit of profit and material progress for both indigenous peoples and the planet’s ecological balance. Kopenawa offers a perspective deeply rooted in interdependence and harmonious coexistence with nature, advocating for a way of life that values communal relationships and respect for alterity. The thesis engages in a profound dialogue between these two perspectives, questioning how Levinas’ and Kopenawa’s ideas may complement each other to provide a richer and more multifaceted understanding of subjectivity. By examining the convergences between Levinasian ethics and Yanomami cosmology, the study not only illuminates the limitations of Western thought but also suggests new directions for contemporary ethics. The research underscores the importance of alterity as the foundation of subjectivity and suggests that the integration of Levinas’ and Kopenawa’s perspectives may offer a pathway to overcoming the crises of alienation and disconnection that pervade modernity. Thus, the thesis contributes to the philosophical discourse on ethics and subjectivity, proposing a paradigmatic reconfiguration that foregrounds alterity and responsibility as central elements for the construction of a more just and harmonious future.
Keywords: Filosofia; Ética levinasiana; Cosmologia Yanomami; Alteridade; Subjetividade; Philosophy; Levinasian ethics; Yanomami cosmology; Alterity; Subjectivity; ACCNPQ::Ciências Humanas::Filosofia